2002
DOI: 10.1073/pnas.012579499
|View full text |Cite
|
Sign up to set email alerts
|

Fractal dynamics in physiology: Alterations with disease and aging

Abstract: According to classical concepts of physiologic control, healthy systems are self-regulated to reduce variability and maintain physiologic constancy. Contrary to the predictions of homeostasis, however, the output of a wide variety of systems, such as the normal human heartbeat, fluctuates in a complex manner, even under resting conditions. Scaling techniques adapted from statistical physics reveal the presence of long-range, power-law correlations, as part of multifractal cascades operating over a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

75
1,384
7
86

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,770 publications
(1,598 citation statements)
references
References 59 publications
75
1,384
7
86
Order By: Relevance
“…Ageing and age-related diseases often accompany a wide-ranging loss of physiological complexity (Kyriazis, 2003). The disruptions of fractal and non-linear physiological properties lead to an increase in regularity and stochasticity, a situation encountered during ageing and age-related diseases (Goldberger et al, 2002). Thus, although this pilot study shows that ApEn might be a helpful tool for recognition of AD, further work must be carried out to examine non-linear EEG activity in other types of dementia.…”
Section: Discussionmentioning
confidence: 90%
“…Ageing and age-related diseases often accompany a wide-ranging loss of physiological complexity (Kyriazis, 2003). The disruptions of fractal and non-linear physiological properties lead to an increase in regularity and stochasticity, a situation encountered during ageing and age-related diseases (Goldberger et al, 2002). Thus, although this pilot study shows that ApEn might be a helpful tool for recognition of AD, further work must be carried out to examine non-linear EEG activity in other types of dementia.…”
Section: Discussionmentioning
confidence: 90%
“…In 1991, we developed a new technique for simultaneous monitoring of the electrocardiogram (ECG) and walking stride rate in order to study the relationship between ECG changes (e.g., arrhythmias, ischemia, mean heart rate, and heart rate variability) and physical activity (e.g., supine, standing, walking, and walking rate) on a beat-by-beat and stride-by-stride basis (Hausdorff, Forman, Pilgrim, Rigney, & Wei 1992). Many investigations had shown that measures of heart rate dynamics and heart rate variability, an indicator of cardiovascular health, are sensitive to alterations in the autonomic nervous system's regulation of heart rate (Goldberger et al, 2002;Ho et al, 1997;Lipsitz, Mietus, Moody, & Goldberger, 1990;Peng et al, 1993). Indeed, one could suggest that the study of heart rate dynamics has turned into a discipline of its own, with literally thousands of research article s on this topic spanning those that have examined the basis for healthy heart rate dynamics to those that have examined clinical utility of measures based on heart rate dynamics.…”
Section: Early Beginnings: a Quantitative Marker Of Gait Instabilitymentioning
confidence: 99%
“…Alternatively, one might suggest that there are short-range correlations in the stride interval such that the current value is influenced by only the most recent stride intervals, but over the long term, the fluctuations are random. A third, less intuitive possibility is that the fluctuations in the stride interval exhibit long-range, fractal-like correlations, as seen in a class of scalefree phenomena including heart rate beat-to-beat fluctuations (Goldberger et al, 2002;Peng et al, 1993;Peng et al, 1998;Peng et al, 1994;Peng et al, 2002). In this case, the stride interval at any instant would 'depend' (in a statistical mechanics sense) on the interval at relatively remote times, and this dependence would decay in a scale-free (fractal-like), powerlaw fashion.…”
Section: First Evidence Of Fractal-like Fluctuations In Gaitmentioning
confidence: 99%
“…Indeed 1/f scaling is interpreted as the best compromise between order and disorder, a hallmark of adaptive and healthy systems, as it has been discovered in many young healthy systems [12,13,14]. Aging and some diseases are in contrast linked to a decrease of the fractal properties, time series deviating from 1/f scaling either towards order (towords Brownian motion) or towards disorder (white noise).…”
Section: -P2mentioning
confidence: 99%